An impulse for development or a symbol of crisis. Changing perceptions of the Tokyo 2020 Olympics following the COVID-19 pandemic - Socha, Marcin (Koszty współczesnych kryzysów, 2021)
The purpose of the chapter is to analyze the economic and political of the Tokyo 2020 Olympic and Paralympic Games, taking into account the critical variable, which is the impact of the COVID-19 pandemic. The analysis is based on statistical data on public sentiment in Japan and abroad, statements by Japanese politicians, business representatives, the media, and other groups involved in organizing the Olympics. The chapter shows that the Tokyo IO failed to meet the expectations of the government, organizers, business, the public, and the international community. Olympics management by the government deepened the crisis of confidence in politicians and consolidated the negative perception of Japan’s economic situation. The deteriorating perception of the Olympics among the Japanese public results from the worsening pandemic situation and the lack of crisis management and effective communication strategy.